2021
DOI: 10.1037/npe0000140
|View full text |Cite
|
Sign up to set email alerts
|

Are consumers cognitive misers? An event-related potential study on decision-making in online purchasing.

Abstract: The notion of cognitive miserliness that people can automatically perceive and sensitively react to cognitive cost in cognitive task completion has been accepted widely. No research has investigated the underlying neural processes associated with consumers' cognitive miserliness. We developed a paradigm for event-related potential (ERP) using online purchase decision-making tasks with high/low cognitive demand to explore consumers' neural responses to different levels of cognitive cost. Participants faced eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…Considering previous studies about purchase intentions mainly involved some endogenous components such as P2, N2, and later positive potential (LPP; Y. Chen & Yang, 2021; Shang et al, 2020; Zubair et al, 2020), this research identified P2, N2, and LPP as three ERP components.…”
Section: Consumer Reviews and Expert Reviewsmentioning
confidence: 97%
See 2 more Smart Citations
“…Considering previous studies about purchase intentions mainly involved some endogenous components such as P2, N2, and later positive potential (LPP; Y. Chen & Yang, 2021; Shang et al, 2020; Zubair et al, 2020), this research identified P2, N2, and LPP as three ERP components.…”
Section: Consumer Reviews and Expert Reviewsmentioning
confidence: 97%
“…Considering previous studies about purchase intentions mainly involved some endogenous components such as P2, N2, and later positive potential (LPP; Y. Chen & Yang, 2021;Shang et al, 2020;Zubair et al, 2020), this research identified P2, N2, and LPP as three ERP components. As one of the main potentials, P2 is a relatively early positive component with a peak latency range from 140-250 ms after the stimulus presentation (Delplanque et al, 2004).…”
Section: Event-related Potentials In This Studymentioning
confidence: 98%
See 1 more Smart Citation
“…This increased cognitive demand, in turn, leads to consumers leaning towards opting for human services instead. In other words, selecting a zoonotic AI triggers deliberative decision‐making, which requires consumers to invest cognitive resources and is thus perceived as a cognitive cost by consumers (Chen & Yang, 2021) due to the AI's unconventional embodiment. In summary, we contend that such deliberative decision‐making scenarios involving zoonotic AI compel consumers to exert cognitive effort, resulting in a reluctance to adopt such zoonotic AI.…”
Section: Theoretical Developmentmentioning
confidence: 99%